Methodology of building cultural and public framework of arctic cities on the example of Salekhard city - N. V. Danilina; A. E. Korobeinikova; A. R. Khazbulatova (Vestnik MGSU)
Introduction. Currently, much attention is paid to the development of the Arctic zone of the Russian Federation. The increased interest in the Russian Arctic is associated not only with the discovery of the Northern Sea Route, but also with the great economic, social, raw materials and tourism potential of the territory. The development of the Arctic city is impossible without taking into account its public spaces, their condition and their connectivity. It is the inseparability of cultural, historical and natural objects of the city that makes it possible to create a sustainable, capable of development cultural and social framework.Materials and methods. The analysis of cultural, historical and natural objects of the Arctic cities was carried out, modern GIS technologies for modelling of the cultural and social framework were used, as approbation of theoretical research, an experiment was conducted on the example of the Salekhard city.Results. The developed methodology makes it possible to determine the cultural and social framework (CSF) of the Arctic city and develop a proposal for improvement. The creation of the cultural and social framework of the Arctic city will help to develop a network of public spaces and provide a link between them, which is extremely important in the complex climatic conditions of the North. The design experiment on the example of the city of Salekhard confirmed the applicability of the methodology.Conclusions. The study showed that the current state of cultural, historical and natural objects of the Arctic cities requires the attention of city planners. It is also obvious that the connectivity of attraction objects in the complex climate of the Arctic cities is a necessary condition for security. The methodology of building a cultural and public framework in the Arctic cities will allow to form a coherent network of public spaces in the city, increase the comfort and safety of the living environment for residents, as well as help to develop tourist routes in the city.